2015
DOI: 10.1158/0008-5472.can-15-1023
|View full text |Cite
|
Sign up to set email alerts
|

JX06 Selectively Inhibits Pyruvate Dehydrogenase Kinase PDK1 by a Covalent Cysteine Modification

Abstract: Pyruvate dehydrogenase kinase PDK1 is a metabolic enzyme responsible for switching glucose metabolism from mitochondrial oxidation to aerobic glycolysis in cancer cells, a general hallmark of malignancy termed the Warburg effect. Herein we report the identification of JX06 as a selective covalent inhibitor of PDK1 in cells. JX06 forms a disulfide bond with the thiol group of a conserved cysteine residue (C240) based on recognition of a hydrophobic pocket adjacent to the ATP pocket of the PDK1 enzyme. Our inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 49 publications
4
69
0
Order By: Relevance
“…Functionally, PDK1 enhances glucose consumption, attenuates lactate production, increases oxygen consumption, and reduces extracellular acidification [16, 5153]. Consistently, our results showed that DIC elevates the glucose uptake and OCR, while decreasing the lactate production and ECAR in SKOV3 and A2780 cells (Fig 2).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Functionally, PDK1 enhances glucose consumption, attenuates lactate production, increases oxygen consumption, and reduces extracellular acidification [16, 5153]. Consistently, our results showed that DIC elevates the glucose uptake and OCR, while decreasing the lactate production and ECAR in SKOV3 and A2780 cells (Fig 2).…”
Section: Discussionsupporting
confidence: 81%
“…Following the 24-h treatment, apoptosis was measured by staining the cells with annexin V and propidium iodide (PI) using the FITC Annexin V Apoptosis Detection Kit from BD Pharmingen (Shanghai, China). The cells were analyzed on a C6 Flow Cytometer, and the signal was quantified using C6 Software and a Workstation Computer (BD AccuriTM), as described previously [16]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations